The convergence of judicial and administrative investigation techniques in French law - Guillard, Antonin (Vilnius University Open Series, 2023)
Unsurprisingly, some of the prerogatives of the judicial police and the intelligence services are common. This is the case of human sources. Other acts, particularly those involving deprivation of liberty or intrusion into private life, are usually the responsibility of the judicial police. The commission of an offence and the control of the judicial authority justify restrictions on fundamental rights. This pattern is now disrupted because intelligence law is copying privacy-invasive mechanisms from the criminal procedure code. The convergence of these fields also has an interactive character, since techniques specifically developed for preventive law have recently been borrowed by repressive law. The legislator therefore uses the investigative techniques of each field to improve the other. This movement has an increasingly competitive character which seems to benefit the intelligence services. At this point, they have the most complex and intrusive acts at their disposal, which erodes the distinction between preventive and repressive action.
Keywords: repression; prevention; criminal procedure; intelligence law; investigation technique; privacy